2007
DOI: 10.1007/s11259-007-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Anthelmintic Effect of Three Formulations of Ivermectin (Oral, Injectable and Pour-on) Against Multiple Anthelmintic-Resistant Haemonchus contortus in Sheep

Abstract: We report the results of investigations that were conducted in a sheep flock in Uttaranchal, India where repeated failure of anthelmintic medication was noted. The study revealed that Haemonchus contortus in sheep had developed resistance to benzimidazoles (fenbendazole, mebendazole and albendazole), imidazothiazole (levamisole) and salicylanide (rafoxanide), while it was fully susceptible to avermectins (ivermectin). Further, the suppression of nematode egg output in faeces of sheep naturally infected with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…High allelic frequency of resistance (r) in adult worms collected from extensively managed sheep and in larvae from intensively managed sheep at Pantnagar, as revealed in the present study (Tables 1 and 2), correlates with our earlier findings at the same place where we tested 3 benzimidazole drugs i.e., fenbendazole, mebendazole and albendazole, and found their efficacies to be 52.3%, 37.3% and 72.3%, respectively using FECRT (Garg et al 2007). The high prevalence of resistant alleles in and around Pantnagar may be attributed to frequent and indiscriminate use of benzimidazole anthelmintics in the area which may have resulted in development of resistance.…”
Section: Discussionsupporting
confidence: 91%
“…High allelic frequency of resistance (r) in adult worms collected from extensively managed sheep and in larvae from intensively managed sheep at Pantnagar, as revealed in the present study (Tables 1 and 2), correlates with our earlier findings at the same place where we tested 3 benzimidazole drugs i.e., fenbendazole, mebendazole and albendazole, and found their efficacies to be 52.3%, 37.3% and 72.3%, respectively using FECRT (Garg et al 2007). The high prevalence of resistant alleles in and around Pantnagar may be attributed to frequent and indiscriminate use of benzimidazole anthelmintics in the area which may have resulted in development of resistance.…”
Section: Discussionsupporting
confidence: 91%
“…Similar observation has also been reported by Uppal et al, (1992), Laha et al, (1999) and Garg et al, (2007). However, Makvana andSingh (2009) andJaiswal et al, (2013) observed ivermectin resistant gastrointestinal nematodes in sheep and goats, respectively from Gujrat and Uttar Pradesh, India, respectively.…”
Section: Resultssupporting
confidence: 77%
“…The prevalence of FBZ and TMS resistance might be due to frequent use of same anthelmintic for a long period (Maingi et al, 1996). In India, this type of resistant H. contortus associated with frequent use of different anthelmintics has also been reported by Uppal et al, (1992), Yadav and Uppal (1993) and Garg et al, (2007).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, even though investigations with ivermectins on internal and external parasites in ruminants and horses are widely documented [18]- [22], the research on the efficacy of pour-on ivermectin formulations in dogs is somewhat scarce [3]- [23]. In Mexico, where disease-carrying IP, fleas and lice in dogs are abundant, no controlled test on the impact of pour-on ivermectin has been carried out, either on the weight differences of treated animals or on the specific identification of the parasites present before and after treatment of the dogs.…”
Section: Introductionmentioning
confidence: 99%